Introducing online exams - Borges, J.; Justino, E.; Vaz, C.; Barroso, J.; Reis, A. (INTED2017 Proceedings, 2017)
To receive a degree from a Higher Education Institution (HEI), the students must successfully undergo the necessary exams, which, most times, requires the physical presence of the student in a room where it will solve and answer the exams’ questions using the traditional pen and paper. This is a well-known and reliable method to evaluate the students, in which the physically presence is a reliable way to diminish the possibilities of fraud. Currently, the modern Learning Management Systems (LMS) are able to provide the necessary features to execute the evaluations activities online, on the software platform. These systems and features can be use in a blended model, in which the students are required to be physically present, in a similar form to a traditional on site exam, and the exam is executed using a LMS. The exam room is equipped with Personal Computers (PC), which are configured with the necessary means to access the LMS and assure that a higher risk of fraud is not introduced by the usage of the PCs and the LMS as support for the exams. We designated this model, as the b-eval model. The adoption of this model requires some changes in the professors’ practices, as well as the introduction of more technological means to support the increase in PCs and LMS usage. The professors must design their evaluation process in order to incorporate the features and restrains posed by the PCs and the LMS. In some scenarios, this adoption is advantageous for the professor and for the students, considering that a properly designed exam can easily be executed by the students and instantaneously evaluated and graded. Otherwise, the traditional process takes much longer, as the professor must collect the paper exams, which he will later evaluate and grade. The process can take several days or even weeks. In this position paper we discuss the introduction of the b-eval model, as well as an assessment methodology for its adoption.